2016
DOI: 10.1073/pnas.1600179113
|View full text |Cite
|
Sign up to set email alerts
|

Kalirin and Trio proteins serve critical roles in excitatory synaptic transmission and LTP

Abstract: The molecular mechanism underlying long-term potentiation (LTP) is critical for understanding learning and memory. CaMKII, a key kinase involved in LTP, is both necessary and sufficient for LTP induction. However, how CaMKII gives rise to LTP is currently unknown. Recent studies suggest that Rho GTPases are necessary for LTP. Rho GTPases are activated by Rho guanine exchange factors (RhoGEFs), but the RhoGEF(s) required for LTP also remain unknown. Here, using a combination of molecular, electrophysiological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
119
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 33 publications
9
119
0
1
Order By: Relevance
“…Indeed, recent evidence suggests that, besides components of native AMPAR complex (Granger et al, 2013), SynGAP and Kalirin/Trio family proteins are other potential CaMKII substrates (Araki et al, 2015; Herring and Nicoll, 2016a). Multiple CaMKII phosphorylation sites were identified in both SynGAP (Araki et al, 2015; Carlisle et al, 2008b; Oh et al, 2004) and Kalirin/Tiam1/Trio family proteins (Fleming et al, 1999; Tolias et al, 2005; Xie et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent evidence suggests that, besides components of native AMPAR complex (Granger et al, 2013), SynGAP and Kalirin/Trio family proteins are other potential CaMKII substrates (Araki et al, 2015; Herring and Nicoll, 2016a). Multiple CaMKII phosphorylation sites were identified in both SynGAP (Araki et al, 2015; Carlisle et al, 2008b; Oh et al, 2004) and Kalirin/Tiam1/Trio family proteins (Fleming et al, 1999; Tolias et al, 2005; Xie et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple CaMKII phosphorylation sites were identified in both SynGAP (Araki et al, 2015; Carlisle et al, 2008b; Oh et al, 2004) and Kalirin/Tiam1/Trio family proteins (Fleming et al, 1999; Tolias et al, 2005; Xie et al, 2007). Molecular replacement of WT protein with SynGAP mutant proteins carrying mutations in CaMKII phosphorylation sites showed impairments in structural plasticity and chemical LTP in primary neurons (Araki et al, 2015) and in LTP in organotypic slice cultures manipulated with Trio/Kalirin (Herring and Nicoll, 2016a). Although multiple CaMKII substrates for LTP may exist, the present study demonstrates that disruption of only TARPγ-8 phosphorylation impairs LTP and performance in a fear-conditioning task.…”
Section: Discussionmentioning
confidence: 99%
“…Trio, on the other hand, is clearly a more dynamic multi-functional protein, with roles in a variety of neuronal compartments, including growth cones, dendritic spines, and the presynaptic AZ. For example, Drosophila studies have demonstrated that Trio is necessary for the effect of retrograde signals at the neuromuscular junction acting on the motor neuron [39], and recent studies in mammalian systems have demonstrated that Trio has roles in regulating AMPA-type glutamate receptors postsynaptically [77]. Therefore, we would expect that, at any one moment in a neuron, only a small percentage of the available Trio would be bound to Piccolo or Bassoon.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Wnt signaling might regulate the interaction of Piccolo, Bassoon, Daam1, and Trio both in young neurons, modulating presynaptic assembly and thereafter, in mature neurons, regulating synaptic plasticity. Finally, a recent paper describing Trio’s role in controlling post-synaptic trafficking events underlying long-term potentiation (LTP) clearly showed redundancy between Trio and the highly related protein Kalirin [77]. Thus, future functional studies on Trio in mammalian systems will need to take into account potential redundancy between Trio and Kalirin.…”
Section: Discussionmentioning
confidence: 99%
“…; Hell ; Shonesy et al . ; Herring and Nicoll ). In this review, we will specifically focus on how enzymatic and structural functions of CaMKII cooperate with each other to facilitate synaptic plasticity of dendritic spines.…”
mentioning
confidence: 98%